Sustainable benefits to sugarcane farmers through a strong ethanol blending programme in India - Roy, M. M.; Chandra, A. (Indian Farming, 2018)
A stable ethanol blending programme in the country will ensuresustainable benefits to the sugarcane farmers, who are frequently affectedin bumper sugarcane crops and itslack of market demand. Suchincentives will motivate small- andmedium-farmers to increase theirefforts towards scientificmanagement sugarcane of crop asthere will be better returns.